2017
DOI: 10.1051/0004-6361/201730452
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of stars around the Milky Way’s central black hole

Abstract: Context. This is the second of three papers that search for the predicted stellar cusp around the Milky Way’s central black hole, Sagittarius A*, with new data and methods. Aims. We aim to infer the distribution of the faintest stellar population currently accessible through observations around Sagittarius A*. Methods. We used adaptive optics assisted high angular resolution images obtained with the NACO instrument at the ESO VLT. Through optimised PSF fitting we removed the light from all dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
102
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(137 citation statements)
references
References 100 publications
24
102
2
2
Order By: Relevance
“…Our study provides the first spectroscopic detection of a cusp of giant stars toward the central arcsecond. This finding agrees with the recent studies found a cusp profile of fainter giants outside the central arcsecond out to 2 pc from the SgrA * (Baumgardt et al 2018;Gallego-Cano et al 2018;Schödel et al 2018).…”
Section: Summary and Discussionsupporting
confidence: 93%
“…Our study provides the first spectroscopic detection of a cusp of giant stars toward the central arcsecond. This finding agrees with the recent studies found a cusp profile of fainter giants outside the central arcsecond out to 2 pc from the SgrA * (Baumgardt et al 2018;Gallego-Cano et al 2018;Schödel et al 2018).…”
Section: Summary and Discussionsupporting
confidence: 93%
“…1 However, diffuse light measurements of Schödel et al (2018) give a lower value γ 1 = 1.13 ± 0.08. The difference in the BH number between γ 1 = 1.5 and γ 1 = 1.1 is only ∼ 15%.…”
Section: 2mentioning
confidence: 96%
“…As anticipated above, we selected two different old stellar populations that may dominate the NRR effects (i.e., the computation of t r ) in our model of the GC: (i) light stars with average mass m = 1 M , slope of the density profile γ NRR = 1.25 and number within the inner parsec N NRR (< 1 pc) = 10 6 ('L' population, Schödel et al 2018;Gallego-Cano et al 2018;Baumgardt et al 2018;Habibi et al 2019); (ii) stellar-mass BHs with average mass m = 10 M , with a steeper density profile (γ NRR = 2) and for which N NRR (< 1 pc) = 10 4 ('H' population, Baumgardt et al 2018;Hailey et al 2018).…”
Section: Stellar Population Dominating Nrr Effectsmentioning
confidence: 99%